Raman spectroscopic identification of size-selected airborne particles for quantitative exposure assessment. (25th February 2016) - Steer, Brian; Gorbunov, Boris; Price, Mark C; Podoleanu, Adrian
Abstract: In this paper we present a method for the quantification of chemically distinguished airborne particulate matter, required for health risk assessment. Rather than simply detecting chemical compounds in a sample, we demonstrate an approach for the quantification of exposure to airborne particles and nanomaterials. In line with increasing concerns over the proliferation of engineered particles we consider detection of synthetically produced ZnO crystals. A multi-stage approach is presented whereby the particles are first aerodynamically size segregated from a lab-generated single component aerosol in an impaction sampler. These size fractionated samples are subsequently analysed by Raman spectroscopy. Imaging analysis is applied to Raman spatial maps to provide chemically specific quantification of airborne exposure against background which is critical for health risk evaluation of exposure to airborne particles. Here we present a first proof-of-concept study of the methodology utilising particles in the 2–4 μ m aerodynamic diameter range to allow for validation of the approach by comparison to optical microscopy. The results show that the combination of these techniques provides independent size and chemical discrimination of particles. Thereby a method is provided to allow quantitative and chemically distinguished measurements of aerosol concentrations separated into exposure relevant size fractions.